Implementasi Akhlak Terhadap Pergaulan Islami pada Remaja - Anisa Maulidani; Fuady Anwar; Wirdati Wirdati (An-Nuha, 2022)
This study aims to explore how the implementation of Islamic social morality in adolescents in Korong Balah Aie. The type of research used is field research or field research, namely research in which data and information are obtained directly in the field. Data were collected through direct interviews with three informants consisting of teenagers, parents, and village officials. To support the interview data, the writer also took observation and documentation data. Interview data were analyzed through the stages of taking, reducing, and presenting data and ending with drawing conclusions. Overall, the results of the study indicate that adolescents do not fully understand and implement Islamic social morals. Related to that, the data actually found that there were eight important indicators related to how the actual application of the concept of Islamic association for moral development for teenagers. The eight indicators are: covering the genitals, staying away from adultery, prohibiting a young couple to be alone, praying, saying good manners, being devoted to parents, smoking bans for teenagers, saying greetings when meeting fellow Muslims. We can use these eight indicators as a reference by teenagers in carrying out Islamic social morality because based on the results of research it has been proven to be able to apply Islamic social morals.